Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1182/blood-2003-04-1044
|View full text |Cite
|
Sign up to set email alerts
|

Profound loss of T-cell receptor repertoire complexity in cutaneous T-cell lymphoma

Abstract: Cutaneous T-cell lymphoma (CTCL) is a malignancy of skin-homing T cells. A major feature of CTCL is profound immunosuppression, such that patients with advanced mycosis fungoides or Sé zary syndrome have been compared with patients with advanced HIV disease and are susceptible to opportunistic infection. The etiology of this immunosuppression is unclear. We analyzed peripheral blood T cells of patients with CTCL with stage I to IV disease, using a sensitive betavariable complementarity-determining region 3 spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 40 publications
8
119
1
4
Order By: Relevance
“…4). In contrast to the previously described limited expression of V␤ by T cells from mycosis fungoides and psoriasis skin lesions, we found no discernable V␤ bias among T cells infiltrating normal skin (11)(12)(13)(14)(15)(16)). …”
Section: Skin Resident T Cells Have a Highly Diverse Tcr Repertoirecontrasting
confidence: 55%
“…4). In contrast to the previously described limited expression of V␤ by T cells from mycosis fungoides and psoriasis skin lesions, we found no discernable V␤ bias among T cells infiltrating normal skin (11)(12)(13)(14)(15)(16)). …”
Section: Skin Resident T Cells Have a Highly Diverse Tcr Repertoirecontrasting
confidence: 55%
“…We have shown in our study that Vb flow cytometry is quantitative, and the quantitative nature of Vb expression can be further improved by incorporating the other immunophenotyping data such as CD4:CD8 ratio, absolute CD3 þ CD4 þ CD26À cells, or CD3 þ CD4 þ cells into the flow cytometric analysis, validating the proposal by earlier pilot studies. 25,37 We have also shown that Sézary cell counting by morphologic analysis is extremely insensitive and would miss a high proportion of cases with a high tumor burden compared with flow cytometric analysis (Figure 4). Using flow cytometric Vb expression analysis, at least 12 patients were upstaged from B1 to B2, a change in peripheral blood stage with prognostic implications.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, CTCL is associated with a significant loss of the T-cell repertoire, analogous to that observed in HIV infection. T-cell receptor (TCR) diversity within multiple TCR beta-variable (Vb) families was analyzed using complementarity-determining region 3 (CDR3) spectratyping and combined with a quantitative analysis of TCR-Vb usage by flow cytometry [58]. In patients with advanced-stage disease, and half of patients with limited-stage disease, a dramatic loss of TCR diversity was observed.…”
Section: Immunopathogenesismentioning
confidence: 99%